20 years of Outcome Mapping - Community, OM Learning (2021)
Celebrate 20 years of Outcome Mapping with the OMLC Stewards plus spec ial guests in this 90 minute webinar. - Exclusive celebration video wi th Outcome Blues soundtrack - Fireside chat with the authors of the OM manual, Sarah Earl, Fred Carden & Terry Smutylo, to hear their views on OM’s evolution since the 2001 publication - Launch of our new paper presenting core concepts of OM and guiding practices for transformati ve change, with special guests Sonal Zaveri & Julius Nyangaga as discu ssants